Distribution Channel Analysis in Increasing Customer Satisfaction - Gea, Nopasti; Gea, Jeliswan Berkat Iman Jaya; Mendrofa, Martha Surya Dinata; Laia, Otanius (Manunggal Halim Jaya, 2024)
The aim of this research is to find out how distribution channels are, the factors that influence distribution channels and distribution channel strategies in increasing customer satisfaction at Lion Parcel Gunungsitoli City. This research uses a qualitative research approach. The sample in this study was 4 people consisting of business owners, admin staff (couriers) and customers at Lion Parcel Gunungsitoli City. The data collection techniques used were observation and interviews. The results of this research are firstly that the distribution channel at Lion Parcel is quite good, prioritizing good service quality and providing convenience in carrying out transactions and bonuses for regular customers, secondly, the factors that influence distribution at Lion Parcel in Gunungsitoli City are the distance that is quite far and the infrastructure does not support it and the courier staff is still minimal and the third is Lion Parcel Gunungsitoli City, namely adding workers so that goods can be distributed properly and looking for other alternatives to speed up the distribution process.